Based on Brand Empowerment and customer Psychology: Lululemon Marketing Strategies Analysis - Jiang, Siying (Transactions on Social Science, Education and Humanities Research, 2024)
With the development of the economy and the advent of the post-pandemic era, people tend to choose healthier lifestyles. Lululemon has won the global sportswear market rapidly. It built excellent product power and brand power. Lululemon profound insight into market development trends and consumer needs then expand its products and services constantly. To stand out from many brands with excellent marketing models. However, there are also some problems like the relatively weak supply chain and potential users losing. Lululemon needs to improve in maintaining its own development and market competitiveness, to better conform to the trend of globalization. Therefore, this research adopts literature review and case analysis methods. Simultaneously, through the study of brand empowerment and consumer psychology. Under the theoretical frameworks of STP, SWOT, and 4P to analyze the reasons for Lululemon has successes in a short time. Meanwhile, this research also gives suggestions on Lululemon’s existing challenges in order to increase the brand’s anti-risk ability and sustainable development. Emerging brands can draw valuable insights from this research.